O absenteísmo-doença em um instituto federal de educação de 2011 a 2018 - Mauro, Leonardo de Souza (2020)
In a federal public service, the investigation of sick leave, granted by the Integrated Subsystem of Civil Servant Health Care, helps to understand sickness absenteeism, phenomenon related to absence of workers from their jobs for health-related issues. It was intended to study the sickness absenteeism in a federal education institution from Rio Grande do Sul (Brazil), determining the indicators, the profile of sick leaves and its time trend from 2011 to 2018, in addition to assessing whether the distribution of licenses by classifications of the Tenth Revision of the International Statistical Classification of Diseases and Health-Related Problems (ICD-10) was associated with demographic variables and occupational of the servers. This was a retrospective epidemiological study with use of a secondary data, equivalent to the sick leaves license records of active employees, located in the Rectory in one of the institute's eleven campuses, which corresponded to 1,478 people in 2018. A secondary data was extracted from management reports of the Personnel Administration System and Integrated Subsystem of Civil Servant Health Care, and were included in Microsoft Office Excel 2010 spreadsheets, one for each year of the study. The determination of sickness absenteeism indicators was based on the model proposed by the Sub-committee on absenteeism of Permanent Comission and Internacional Association on Occupational Health. Regarding demographic variables, the gender was categorized as male or female and the ages of the employees were aggregated in the following groups: ≤25, 26-30, 31-35, 36-40, 41-50, 51-60, ≥ 61 years. Regarding occupational variables, the position of the servers was categorized as Technical-Administrative in Education (TAE) or teaching, and the capacity was according to the location of the server. To verify the distribution of sick leaves for ICD-10 codes was associated with demographic and occupational variables, Fisher's exact test was performed, with p-value <0.001. In addition, the principal component analysis was carried out, which made it possible to identify which associations were most significant. The number of sickness absenteeism license was consistent with the growth in the number of employees at the institution and the average absenteeism-disease rate was 2.27%. Mental disease, obstetric and musculoskeletal diseases were the most frequent, equivalent to 26.06%, 13.68% and 7.71% of sick leaves, in that order. There was an association between variables and four ICD-10 code groups, standing out from mental illnesses. In the period, 73.14% of the LMS were for females, 26.85% for the age group 31-35 years, 54.41% for the TAE position and 21.25% for the staff with the largest number of employees. In the trend analysis, the regressions indicated a mostly increasing pattern and, when comparing the angular coefficients, statistically higher growth rates were found in the female gender and age groups between 31 and 50 years. There’s no significant difference in growth for positions, exposing a similar trend for Technical-Administrative in Education and teachers. It’s suggested the need for institutional interventions, especially in the area of mental health and quality of life, seeking to change the values of sickness absenteeism indicators.